Productive Government Expenditure in Monetary Business Cycle Models - Ludger Linnemann; Andreas Schabert (Tinbergen Institute, 2005)
This paper assesses the transmission of fiscal policy shocks in a New Keynesian framework where government expenditures contribute to aggregate production. It is shown that even if the impact of government expenditures on production is small, this assumption helps to reconcile the models' predictions about fiscal policy effects with recent empirical evidence. In particular, it is shown that government expenditures can cause a rise in private consumption, real wages, and employment if the government share is not too large and public finance does not solely rely on distortionary taxation. When government expenditures are partially financed by public debt, unit labor costs fall in response to a fiscal expansion, such that inflation tends to decline. Households are willing to raise consumption if monetary policy is active, i.e. ensures that the real interest rate rises with inflation. Otherwise, private consumption can also be crowded-out, as in the conventional case where government expenditures are not productive. The interaction between monetary and fiscal policy is thus decisive for the short-run macroeconomic effects of government expenditure shocks.
Keywords: E62; E21; E32; 330; Productive government expenditures; private consumption; distortionary taxation; monetary and fiscal policy interaction; Öffentliche Ausgaben; Gesamtwirtschaftlicher Konsum; Konjunkturpolitik; Neukeynesianische Makroökonomik; Konjunkturtheorie; Theorie